The role of tourism in the economy (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
Tourism is vital for the success of many economies around the world. There are several benefits of tourism on host destinations. Tourism boosts the revenue of the economy, creates thousands of jobs, develops the infrastructures of a country, and plants a sense of cultural exchange between foreigners and citizens.